Diagnosis and Management of a Unilateral Posterior Open Bite Using a Temporary Anchorage Device (TAD): Case Report and Review of the Literature - Bandar Alyami (Case Reports in Dentistry)
This report describes the diagnosis and successful treatment of a unilateral posterior open bite (POB) in a 15-year-old Caucasian boy. Simple mechanics were used to rule out ankylosis of left posterior teeth as the etiological factor of the POB. Thereafter, the same mechanics were continued to expand the unilateral constricted maxilla, to create a space, and to close POB. Sectional biomechanics were applied to avoid undesirable tooth movements. Then, continuous arch wires were employed to coordinate arches and to achieve treatment objectives.